The islamic Manuscripts Oskar Rescher Sold to the National Library of the Czech Republic between 1926-1946 - DOĞAN AVERBEK, GÜLER (My University, 2023)
Oskar Rescher was an active Orientalist of the 20th century and, apart from his scientific studies and the duties he had taken on in various institutions, was engaged in the book trade for many years, having sold manuscripts as well as printed books to institutions in the West since 1913. This trade activity lasted practically until his death. One of the institutions to which Rescher sold manuscripts was the National Library of the Czech Republic in Prague. Home to approximately 15,000 manuscripts, the library contains a total of 687 volumes of manuscripts in Turkish, Arabic and Persian. Of these, 245 had been included in the collection through Rescher. However, the regulations the library placed, as well as the requests it voiced, must have been so unsuitable to the dynamics of the trade network Rescher had established and speedily managed with other libraries that he had attempted to cease affairs at the start of the trade relationship. The manuscript trade between Rescher and Prague took place between 1926 and 1946 with interruptions. I have examined the manuscripts Rescher sold to the National Library of the Czech Republic through my studies that have been carried out in the library’s Department of Manuscripts and Early Printed Books and the National Library Archive, prepared a list of manuscripts, and included the obtained results in the article. This study also discusses the prominent features of the manuscripts and presents the manuscript list at the end.

20. yüzyılın aktif müsteşriklerinden Osman Reşer, ilmî çalışmalarının ve muhtelif kurumlarda üstlendiği vazifelerin haricinde uzun yıllar kitap ticaretiyle meşgul olmuş, basma kitapların yanı sıra 1913 senesinden itibaren yazma kitapları da Batı’daki kurumlara satmıştır. Bu ticari faaliyet neredeyse vefatına kadar sürmüştür. Reşer’in yazma sattığı kurumlardan biri de Prag’da bulunan Çek Cumhuriyeti Millî Kütüphanesi’dir. Yaklaşık 15.000 yazma esere ev sahipliği yapan kütüphanede Türkçe, Arapça ve Farsça toplam 687 cilt yazma bulunmaktadır. Bunların 245 adedi Reşer aracılığıyla koleksiyona dâhil olmuştur. Fakat kütüphanenin koyduğu kaideler ve dile getirdiği talepler, pek çok kütüphane ile kurduğu ve hızlı bir şekilde idare ettiği ticaret ağı dinamiğine uygun gelmemiş olmalı ki Reşer, henüz ticari ilişkinin başında bu işten çekilmeyi denemiştir. ReşerPrag arasındaki yazma ticareti inkıtalarla birlikte 1926-1946 yılları arasında cereyan etmiştir. Çek Cumhuriyeti Millî Kütüphanesi, Yazmalar ve Nadir Eserler Bölümü’nde ve Millî Kütüphane Arşivi’nde bizzat yürüttüğümüz çalışmalar ile Reşer’in Çek Cumhuriyeti Millî Kütüphanesi’ne sattığı yazmaları ve bunların satış sürecini gösteren yazışmaları inceledik, yazmaların listesini hazırladık ve ulaşılan neticeleri bu yazıya derc ettik. Bu çalışmada ayrıca yazmaların öne çıkan hususiyetleri ele alınmış ve çalışmanın sonunda yazmaların bir listesi sunulmuştur.
Osman Reşer’in 1926-1946 yıllarında Çek Cumhuriyeti Millî Kütüphanesi’ne sattığı islâm yazmaları
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Türk Dili ve Edebiyatı; Eski Türk Edebiyatı; Doğu Dilleri ve Edebiyatları; Arap Dili ve Edebiyatı; Fars Dili ve Edebiyatı; Social Sciences and Humanities; Philology; Turkish Language and Literature; Old Turkish Literature; Eastern Languages and Literatures; Arabic Language and Literature; Persian Language and Literature; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities; Oskar Rescher; İslâm yazmaları; yazma ticareti; Çek Cumhuriyeti Millî Kütüphanesi; Osman Reşer; Islamic manuscripts; manuscript trade; National Library of the Czech Republic